Diversity of avenanthramide content in wild and cultivated oats - S. Leonova; A. Gnutikov; I. Loskutov; E. Blinova; K.-E. Gustafsson; O. Olsson (Труды по прикладной ботанике, генетике и селекции)
Background. Oat grains accumulate substantial amounts of various phenolic compounds that possess biological activity and have a potential to considerably increase health benefits of oats as a food. Avenanthramides (AVA) is an important group of these compounds due to their antioxidant, anti-itching, anti-inflammatory, antiproliferative activities.Materials and methods. Using combined HPLC and LC-MS analyses, we provide the first comprehensive review of the total avenanthramide content and composition in cultivated and wild oats. The AVA content was measured in 32 wild and 120 cultivated oat accessions obtained from the global collection of the N.I. Vavilov Institute of Plant Genetic Resources (VIR), St. Petersburg, Russia.Results and conclusion. The wild hexaploid A. sterilis L. had the highest total AVA content, reaching 1825 mg kg–1. Among cultivated accessions, naked oat cv. ‘Numbat’ (Australia) had the highest AVA content, 586 mg kg–1. The AVA composition exhibited a wide diversity among the analyzed samples. Accessions were identified where AVAs A, B and C, which are generally considered as major AVA, had a low percentage, and instead other AVAs prevailed. The AVA content in eight oat cultivars revealed significant annual changes in both the total AVA content and the proportions of individual AVAs. Using HPLC analyses, 22 distinguishable peaks in AVA extracts of oat seeds were detected and quantified. Several of these peaks, which have not been previously documented, presumably represent different AVAs. Further analyses are needed to detail these findings and to determine the specific AVA structures in oat grains.